Associations between human TRIM22 gene expression and the response to combination therapy with Peg-IFN[alpha]-2a and ribavirin in Iranian patients with chronic hepatitis C - Sadeghi, Farzin; Bokharaei-Salim, Farah; Salehi-Vaziri, Mostafa; Monavari, Seyed Hamidreza; Alavian, Seyed Moayed; Salimi, Shima; Vahabpour, Rouhollah; Keyvani, Hossein (Journal of medical virology, 2014)
Interferons are able to exert an antiviral effect against hepatitis C virus (HCV) infection via induction of interferon-stimulated genes (ISGs). This study tested whether differential expression of an important ISG with antiviral properties, tripartite motif 22 (TRIM22), correlates with a response to Peg-IFN[alpha]-2a/RBV combination therapy in treatment-naive patients with chronic hepatitis C. A total of 32 patients with chronic hepatitis C were enrolled in this study and received standard Peg-IFN[alpha]-2a/RBV combination therapy. HCV viral load was measured during treatment, at the end of treatment, and 6 months later to determine the treatment outcome. Quantitative real-time PCR was used to assess the expression levels of TRIM22 in peripheral blood mononuclear cells (PBMCs) of the patients before antiviral therapy. Of the 32 patients, 26 (81.3%) were males. In this study, there were 16 (50%) individuals with a sustained virologic response (SVR), and a virologic relapse was observed in the remaining half of the subjects. Testing for the presence of genomic HCV RNA in blood during therapy revealed a rapid virologic response (RVR) in 10 (31.2%) and a partial and complete early virologic response (EVR) in 8 (25%) and 24 (75%) of the cases, respectively. TRIM22 mRNA levels were significantly higher in patients with a sustained virologic response than in relapsers (P=0.002) and in patients with a rapid virologic response than in the others (P=0.040). No statistically significant difference was seen in the expression of TRIM22 between patients with a partial early virologic response and a complete early virologic response. This study showed that pretreatment upregulation of TRIM22 may be associated with responsiveness to Peg-IFN[alpha]-2a/RBV combination therapy. J. Med. Virol. 86:1499-1506, 2014. © 2014 Wiley Periodicals, Inc. [PUBLICATION ABSTRACT]